2016
DOI: 10.1177/0300060516667118
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital coronary artery anomalies as shown by multi-slice computed tomography coronary angiography: a single-centre study from Turkey

Abstract: ObjectiveCoronary artery anomaly (CAA) is a remarkable etiological factor for sudden cardiac death in young adults. The incidence of CAA is unknown, with most reliable data available based on postmortem/angiography investigations. This study aimed to assess the prevalence of different forms of coronary anomalies, and to investigate the relationships between demographic data and occurrence of CAA.MethodsA total of 2401 consecutive patients (1805 men; mean age, 56 ± 11.7 years), who were referred between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Another study by Chaiyagool et al [7] showed almost double prevalence of coronary anomalies (61.6%). On the other side, the present study results were higher than those of Tongut et al [4] with prevalence of 10%.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Another study by Chaiyagool et al [7] showed almost double prevalence of coronary anomalies (61.6%). On the other side, the present study results were higher than those of Tongut et al [4] with prevalence of 10%.…”
Section: Discussioncontrasting
confidence: 91%
“…The present study included 7 patients with abnormal origin of right coronary artery from left coronary sinus out of 630 patients (1.1%). Rao et al [5] reported those anomalies in 0.6% and Tongut et al, 2016 [4] reported them in 0.5% of the studied cases.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Prevalence of anomalies of origin and of course was 1.02%, similar to what has been reported in other studies. 14,19 MBLAD, a 9.7% prevalence in our study, was considered a normal anatomic variant in other studies. When this anomaly is excluded, the prevalence of CA found in our study decreases to 1.27%, showing that, when such anomaly is considered, the result of the study can change.…”
Section: Discussionmentioning
confidence: 61%
“…Several studies only consider anomalies of origin and course, based on the Angelini et al classification 3 , or only disregard MBLAD as anomaly. [12][13][14][15][16][17][18][19] In addition, there are studies that use their own classification, [20][21][22][23] making it challenging to compare data unless one performs a re-analysis of the results using the same classification.…”
Section: Discussionmentioning
confidence: 99%